Encyclopedia of the sciences of learning - Seel, Norbert M.
"The Encyclopedia of the Sciences of Learning provides an up-to-date, broad, and authoritative coverage of theories and philosophies used in the sciences of learning and adjacent sciences from their very beginnings to the present. This modern compendium is an indispensable source of information for scientists, educators, engineers, and technical staff active in all fields related to the learning of animals, humans, or machines ... It supplies clear and precise explanations of the theoretical terms, cross-references to related content, and up-to-date references to important research and publications."--Pref
"With 312 Figures and 68 Tables"--T.p. - Includes bibliographical references and index